Strategy for Reforming the Banking System of the Republic of Uzbekistan - Sh. N., Sadikov (International Journal on Integrated Education, 2023)
On May 12, 2020, Decree of the President of the Republic of Uzbekistan No. PF-5992 "On the strategy for reforming the banking system of the Republic of Uzbekistan for 2020-2025" was adopted. The Resolution approved the Strategy for Reforming the Banking System of the Republic of Uzbekistan for 2020-2025, the Road Map for Reforming the Banking System of the Republic of Uzbekistan, as well as target indicators for the implementation of the strategy.